The Influence of Health Education Using Booklet Media on the Level of Knowledge and Attitudes of Young Women About Anemia at Mts Raudlatul Ulum Langkap Besuki Situbondo - Qomariyah, Nurul; Andayani, Astutik; Tauriana, S (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Introduction: One of the problems that often arises in young women is anemia. Knowledge about anemia will influence the attitudes and behavior of young women in preventing anemia. Research objective: to determine health education using booklet media on the level of knowledge and attitudes of young women regarding anemia. Method: using a Quasi Experimental design with a pretest-posttest design and a control group. The research sample consisted of 48 young women at MTS Raudhatul Ulum which were divided into 24 intervention groups and 24 control groups. The measuring instrument used was a questionnaire in the form of a knowledge and attitude questionnaire. Research results: Test results in the control group, statistical tests on knowledge produces a p-value of 0.009 (>0.05), which means the null hypothesis (Ho) is accepted. These results indicate that there was no significant change in the control group's knowledge after the research was conducted. However, in the intervention group, statistical tests on knowledge and attitudes in the intervention group showed p-values of 0.000 (<0.05) and 0.001 (<0.05), respectively, which means the alternative hypothesis (Ha) was accepted. This indicates that health education using booklet media has a significant positive influence on the knowledge and attitudes of young women about anemia.